Obvladovanje pojava invazivnih rastlin (neofitov) in ohranjanja biodiverzitete na vodovarstvenih območjih - Lešnik, Mario (University of Maribor Press, 2017)
Management of Invasive Plants (Neophytes) and Biodiversity Preservatio in Water Protection Areas. One of the consequences of adjusting agricultural production techniques to protect water in water protection areas (WPA), is a significant reduction in the intensity of crop production or even the abandonment of land cultivation (especially land situated directly near vulnerable water sources). Inadequately maintained land begins to turn into low-quality grasslands, which turns into semi-natural plant communities in the next phase, often composed of invasive alien plants. Experience has shown that populations of invasive plants increase faster in WPA than in areas without water protection measures, and where farmers practice intensive crop production and good management practices of semi-natural habitats. In this monograph, we tried to present part of the invasive plant species already present in the territory of Slovenia (also at Mura river basin), or are expected to appear in the near future. Due to the lack of information, the awareness about the harmfulness of invasive alien plant species is low. Practical advice on the methods of controlling different invasive species are presented. We pointed out the need for proper maintenance of semi-natural habitats directly neighboring agricultural fields, which are otherwise intended to protect the water and conserve biotic diversity, but also have important biological functions for the conservation of organisms that regulate natural processes vital for the success of crop production. Preventive action against invasive plants is, economically and ecosystematically, most effective. Allowing uncontrolled development of invasive plants at WPA can result in long-term destabilization of semi-natural habitats, as well as increase the costs of agricultural crop production and the cost of maintaining energy, transport and hydrological infrastructure of the agricultural landscape in the future.